Everyday life activities and well-being: Their relationships with age and gender in the elderly - Meléndez, Juan Carlos; Tomás, José Manuel; Navarro, Esperanza (Anales de Psicología / Annals of Psychology, 2010)
Present study deals with the relationships among everyday life activities and well being with age and gender in the elderly. Research design was a cross-sectional survey of a sample of 566 elderly living in the Province of Valencia (Spain). These participants were surveyed on several dimensions, including socio-demographic information, everyday life activities (Barthel’s index) and Ryff’s Scales of Well-being. Main results with respect to everyday life activities were: a) positive relationships between well-being dimensions and Barthel’ index; b) negative relationships between age and Barthel’s index; and finally, c) higher Barthel’s index for men than for women. With respect to Ryff’s dimensions of well being, results also showed negative relationships of age with all dimensions, but these negative relations were larger for psychological dimensions than for subjective dimensions. There were also statistically significant gender differences in autonomy, personal growth and self-acceptance: men scored higher on the aforementioned well-being dimensions.